2022
DOI: 10.3390/antibiotics11050667
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Antimicrobial Stewardship Optimization: The Use of Antibiotics in Humans and Animals to Prevent Resistance

Abstract: Antimicrobials are a type of agent widely used to prevent various microbial infections in humans and animals. Antimicrobial resistance is a major cause of clinical antimicrobial therapy failure, and it has become a major public health concern around the world. Increasing the development of multiple antimicrobials has become available for humans and animals with no appropriate guidance. As a result, inappropriate use of antimicrobials has significantly produced antimicrobial resistance. However, an increasing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 173 publications
0
21
0
Order By: Relevance
“…The Basic Information of ANTs. ANTs, the archetypal representatives of the tetracyclic type II polyketide natural antibiotics [39][40][41], were initially isolated from the bacterium Streptomyces peucetius and showed remarkable anticancer activities [42]. The first ANT was named daunorubicin (DNR) and was applied to acute leukemia treatment in 1963 [43].…”
Section: Discussionmentioning
confidence: 99%
“…The Basic Information of ANTs. ANTs, the archetypal representatives of the tetracyclic type II polyketide natural antibiotics [39][40][41], were initially isolated from the bacterium Streptomyces peucetius and showed remarkable anticancer activities [42]. The first ANT was named daunorubicin (DNR) and was applied to acute leukemia treatment in 1963 [43].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the structural similarities with the natural 3D structure of the extracellular matrix, hydrogels have excellent potential in the cell therapy approach. Hydrogels with cell encapsulation promote desired tissue-specific biomechanical and biochemical characteristics that can control cellular functions [ 216 , 217 ]. Properties like biocompatibility and biodegradability are also crucial for applications of hydrogels in cell delivery [ 218 ].…”
Section: Applications Of Functional Thermo-responsive Hydrogelsmentioning
confidence: 99%
“…The rising body of evidence demonstrates the close relationship between glia and neuronal cells, as well as their impact on neurons. Several studies have found that metabolic changes in glial cells modify neuron-glial connections, hence amplifying the pathophysiology of many neurological illnesses [19][20][21][22][23]. In preliminary research on neurodegenerative, ischemic brain injury, and demyelinating illnesses, glial metabolism was found to have a lower oxidative burden, lower generation of proinflammatory cytokines, and less neuronal damage.…”
Section: Introductionmentioning
confidence: 99%